2002
DOI: 10.1126/science.1076064
|View full text |Cite
|
Sign up to set email alerts
|

Direct Link Between mhc Polymorphism, T Cell Avidity, and Diversity in Immune Defense

Abstract: Major histocompatibility complex (mhc)-encoded molecules govern immune responses by presenting antigenic peptides to T cells. The extensive polymorphism of genes encoding these molecules is believed to enhance immune defense by broadening the array of antigenic peptides available for T cell recognition, but direct evidence supporting the importance of this mechanism in combating pathogens is limited. Here we link mhc polymorphism-driven diversification of the cytotoxic T lymphocyte (CTL) repertoire to the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
276
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(286 citation statements)
references
References 32 publications
10
276
0
Order By: Relevance
“…Higher TCR avidity has been proposed to be critical for the control of viral infections (50)(51)(52) or subsequent infections with related pathogens (40). Of note, we have also shown that the large TRB repertoire renewal observed after treatment interruption and Ag re-exposure may be associated with the increase of functional avidity of T cell recognition.…”
Section: Discussionsupporting
confidence: 55%
“…Higher TCR avidity has been proposed to be critical for the control of viral infections (50)(51)(52) or subsequent infections with related pathogens (40). Of note, we have also shown that the large TRB repertoire renewal observed after treatment interruption and Ag re-exposure may be associated with the increase of functional avidity of T cell recognition.…”
Section: Discussionsupporting
confidence: 55%
“…After refolding with the mouse K d H and L chains, the peptide was able to bind with murine MHC class I molecules. MHC class I molecules, possessing high degrees of polymorphism as the result of the evolutionary process, are able to present various antigenic determinants to host T cells for induction of host immune responses to combat the invading foreign pathogens, such as viruses (32). The epitopes recognized by MHC molecules are believed to be between eight and 12 aa.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have important implications for designing vaccines aimed at promoting the magnitude and breadth of what are normally "minor" responses. This, in turn, may be advantageous for efficient viral clearance as well as the prevention of viral escape (4,5,53). The same arguments may apply to tumor immunity.…”
Section: Figurementioning
confidence: 94%